Housing stability and diabetes among people living in New York city public housing. (August 2020) - Lim, Sungwoo; Liu, Sze Yan (Sam); Jacobson, Melanie H; Poirot, Eugenie; Crossa, Aldo; Locke, Sean; Brite, Jennifer; Hamby, Elizabeth; Bailey, Zinzi; Farquhar, Stephanie
Abstract: Public housing provides affordable housing and, potentially, housing stability for low-income families. Housing stability may be associated with lower incidence or prevalence and better management of a range of health conditions through many mechanisms. We aimed to test the hypotheses that public housing residency is associated with both housing stability and reduced risk of diabetes incidence, and the relationship between public housing and diabetes risk varies by levels of housing stability. Using 2004-16 World Trade Center Health Registry data, we compared outcomes (housing stability measured by sequence analysis of addresses, self-reported diabetes diagnoses) between 730 New York City public housing residents without prevalent diabetes at baseline and 730 propensity score-matched non-public housing residents. Sequence analysis found 3 mobility patterns among all 1460 enrollees, including stable housing (65%), limited mobility (27%), and unstable housing patterns (8%). Public housing residency was associated with stable housing over 12 years. Diabetes risk was not associated with public housing residency; however, among those experiencing housing instability, a higher risk of diabetes was found among public housing versus non-public housing residents. Of those stably housed, the association remained insignificant. These findings provide important evidence for a health benefit of public housing via housing stability among people living in public housing. Highlights: Public housing residency is associated with stable housing. There is no association between public housing residency and diabetes risk. Yet, higher diabetes risk is found among unstably-housed public housing residents.